TRANSFORMATIONAL LEADERSHIP OF ISLAMIC ELEMENTARY SCHOOL PRINCIPALS IN STRENGTHENING EDUCATIONAL QUALITY: A CASE STUDY AT SD ISLAM AL MUTTAQIN - Jamilus Jamilus; Rifka Febrina; Nurmaningsih Yani; Rinto Hutabarat (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to analyze the relationship between the principal's transformational leadership style and the strengthening of quality culture based on Islamic values at SD Islam Al Muttaqin. The study seeks to understand how spiritual and moral values are integrated into the educational quality management system. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation involving principals, teachers, and parents. Data analysis used Miles and Huberman's model consisting of data reduction, data display, and verification. The results revealed that transformational leadership, emphasizing idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration, successfully fostered a sustainable quality culture. Field data showed improved teacher discipline, high parental satisfaction, and consistently good student assessment outcomes. This study can be applied in Islamic educational institutions, school management, and educational leadership development programs to strengthen both academic and spiritual quality systems in Islamic elementary schools and madrasahs. This study combines transformational leadership theory with Islamic values in the context of educational quality culture. The findings contribute to new insights into how spiritual dimensions can reinforce holistic and sustainable school quality management practices.